Improving Student Learning Outcomes in Natural Science Learning Through Image Cutouts in Class V - Nurasih, Siti (Universitas Sebelas Maret, 2020)
The research conducted is to improve the learning outcomes of students in learning. Student learning outcomes are very influential on the delivery of learning and the way the learning is carried out, in learning supporting media is needed to support learning success. This research is a classroom action research (PTK) obtained from the results of research on teacher activity through 3 cycles, namely in cycle I with an average value of 57 (less) and in cycle II to 69 (sufficient), while in cycle III it has increased by 78, 8 (good). Student learning outcomes obtained in science learning, namely, cycle I and cycle II the value has not been completed because it has not reached the KKM, while in cycle III with the use of cutout media in learning, there were 18 students with an average value of 78.8 or 86%. have reached KKM and 3 students have not reached the minimum completeness. Based on the results of the data analysis, it can be concluded that the use of cutout media can improve student learning outcomes in science learning in class V SDN Srengseng 01.